Irreversible Adsorption Deformation of Layer Structures - Volodymyr V. Kutarov; Yuri I. Tarasevich; Eugene V. Aksenenko (Adsorption Science & Technology)
In the framework of macroscopic thermodynamics of deformation, expressions are proposed for the calculation of deformation isotherms along the adsorption and desorption branches of the hysteresis loop within the linear and elastic deformation domains. With the assumption of spatially homogeneous (in the statistical sense) medium and scale-invariant behaviour of the relaxation rate, the generalized equation is proposed for the calculation of the hysteresis loop throughout the entire range of the adsorbate pressure in the bulk phase. In this equation, the irreversibility parameter is the governing one. The proposed equations are verified for the benzene adsorption–desorption isotherm on the organosubstituted synthetic fluorhectorite.